Groundwater Temperature Map for Potential Heat Pump in Mueang Chiang Mai District, Chiang Mai Province - Chanakan Wisessan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study focuses on groundwater temperature distribution and groundwater quality of 45 shallow wells at depth less than 10 meters, in Mueang Chiang Mai district. Groundwater temperature and groundwater quality are essential parameters in evaluating the suitability of heat pump installation application. In a heat pump system, groundwater is used as a heat carrier or heat sink to provide space cooling during hot season as air conditioning. Groundwater temperature must be constant and lower than atmospheric temperature. Groundwater quality is assessed using the values of hardness, alkalinity, total dissolved solid and pH to calculate the Langelier Saturation Index (LSI) and the Ryznar Stability Index (RSI) to make a qualitative determination of installing heat pump.